Agriculture in a changing climate: Keeping our cool in the face of the hothouse. (December 2018) - Thornton, Philip; Dinesh, Dhanush; Cramer, Laura; Loboguerrero, Ana Maria; Campbell, Bruce
The challenges facing agriculture in the coming decades are daunting. Recent research suggests that the impacts of climate change on agriculture and food systems may be wider-ranging than previously understood. Can feasible pathways to a food secure and sustainable future be identified? The scale of change required to meet the sustainable development goals, including those of no poverty, zero hunger and the urgent action needed to address climate change, will necessitate the transformation of local and global food systems. We identify eight elements of a theory of change to drive such transformation and highlight four pathways by which transformation may occur. We conclude with some suggestions for 'business unusual' for agricultural research for development.